Formation and Development of a Healthy Lifestyle - Amirkulovna, Arashova Gulnora (Miasto Przyszłości, 2024)
This article explores traditional ideas about a healthy lifestyle and highlights its fundamental philosophical, religious, and worldview meanings. The connection between a healthy lifestyle and social norms and social practices has been determined. The main attention is paid to the social and personal foundations of a healthy lifestyle.